Pengembangan Internet Gateway Device berbasis Koneksi GPRS untuk Mengoleksi dan Meneruskan Data ke Media Penyimpanan - Maxi Luckies Ginanjar Azis; Eko Sakti Pramukantoro; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Implementation of an IoT system for monitoring office environment with temperature and humidity and also with camera sensor meet a problem when data from the middleware can't be forwarded to the internet located storage media because still use local intranet network communication. This problem can be solved by adding internet gateway device functioned as a data collector and forward data to the storage media with GPRS connection. From these requirements, this paper developed mechanism for collecting data and forward data from the middleware to the storage media through GPRS connection with two scenarios, the first scenario used waiting time and the second scenario used direct sending mechanism. The results show that the developed internet gateway device can collect and forward data to the storage media with good performance based on the result functionality testing.